Maturity modelling integrated with apatite fission-track dating: Implications for the thermal history of the Mid-Polish Trough (Poland) - Resak, Marta; Glasmacher, Ulrich A.; Narkiewicz, M.; Littke, R. (Marine and petroleum geology, 2010)
The Mid-Polish Trough (MPT) is situated in the easternmost part of the Central European Basin System (CEBS) and stretches NW-SE across the Polish Basin. It was characterised by pronounced subsidence and thick sediment accumulation between the Permian and the Late Cretaceous. Late Cretaceous-early Paleogene basin inversion led to the formation of the Mid-Polish Swell (MPS). The study area is located within the Pomeranian segment of the MPT/MPS (NW Poland) and experienced up to 7 km Permian-Mesozoic subsidence. PetroMod 1-D modelling was performed on several well-sections in order to study Permian to recent burial-uplift evolution. The modelling was calibrated with new vitrinite reflectance (VRr) data and allowed to constrain the magnitude of uplift and related erosion as well as provided a first overview of the temperature history. The base of the studied Permian-Mesozoic successions attained maximum burial depths of 4800-5400 m before the onset of the inversion, less than in the axial trough area. The thickness of pre- and most probably also syn-inversion Upper Cretaceous deposits is estimated as 300 m. Erosion associated with inversion processes removed between 900 and 1400 m of the Mesozoic sediments, i.e. 1000-1500 m less than in the most inverted central part of the trough. VRr data suggest constant Permian-Mesozoic heat flows corresponding to present-day values (40-45 mW/m2). Apatite fission-track (AFT) ages modelled with the PetroMod module PetroTracks show a good fit with AFT ages directly measured on well samples, and further support the assumption of steady heat flow in the range 40-45 mW/m2. Palaeotemperatures appear to have decreased towards the East European Craton margin, which is compatible with the present day distribution of heat flow. Thermal history modelling shows a relatively simple Permian-Mesozoic heat flow pattern in the Pomeranian segment of the MPT. Such a scenario implies that the present-day heat flow distribution has not changed essentially since Mesozoic times.